cTBS over ventral cortex enhances depth perception - Or, Justin K. N.; Chang, Dorita H. F. (Frontiers in Neuroscience, 2024)
Stereoscopic capacities vary widely across the normal population. It has become increasingly apparent, however, that mechanisms underlying stereoscopic depth perception retain a considerable degree of plasticity through adulthood. Here, we contrast the capacity for neurostimulation in the form of continuous theta-burst stimulation (cTBS) over strategically-chosen sites in the visual cortex to bring about improvements in stereoscopic depth perception. cTBS was delivered to occipital cortex (V1/V2), lateral occipital complex (LOC), along with a control site (Cz). We measured performance on depth and luminance discrimination tasks before and after stimulation. We found a significant improvement in depth (but not luminance) discrimination performance following cTBS over LOC. By contrast, cTBS over occipital cortex and Cz did not affect performance on either task. These findings suggest that ventral (lateral-occipital) cortex is a key node for governing plasticity of stereoscopic vision in visually normal human observers. We speculate that cTBS exerts inhibitory influences that may suppress internal noise within the nervous system, leading to an improved read-out of depth features.